ETHOLOGICAL-TROPHIC GROUPS OF BIVALVE MOLLUSKS AND THEIR DISTRIBUTION IN THE PHANEROZOIC - Nevesskaja L.A. (My University, 2006)
Based on their adaptations to substrates, degree of mobility, and feeding modes, bivalve mollusks are subdivided into 30 ethological-trophic groups. This paper presents an account of their morphological characteristics, distribution in the Phanerozoic, and taxonomic changes through time.